2023
DOI: 10.3389/fpls.2023.1210309
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and transcriptomice analyses of flavonoid biosynthesis in apricot fruits

Abstract: IntroductionFlavonoids, as secondary metabolites in plants, play important roles in many biological processes and responses to environmental factors.MethodsApricot fruits are rich in flavonoid compounds, and in this study, we performed a combined metabolomic and transcriptomic analysis of orange flesh (JN) and white flesh (ZS) apricot fruits.Results and discussionA total of 222 differentially accumulated flavonoids (DAFs) and 15855 differentially expressed genes (DEGs) involved in flavonoid biosynthesis were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
1
2
1
Order By: Relevance
“…In addition, another report revealed that the anthocyanin content in mature P. humilis fruit was significantly positively correlated with ChCHS, ChFLS and ChUFGT expression [42]. Our findings were inconsistent with the previous results that expression of CHS and CHI genes was positively correlated with flavonoid accumulation in citrus and apricot [43,44]. Although 'Nongda 5' had low expression of flavonoid biosynthetic genes and relatively lower total flavonoid contents compared to 'Jinou 1' and 'Nongda 3', its antioxidant abilities were higher than many fruit species [45], suggesting there might be some other bioactive compounds that contribute to its high antioxidant abilities.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, another report revealed that the anthocyanin content in mature P. humilis fruit was significantly positively correlated with ChCHS, ChFLS and ChUFGT expression [42]. Our findings were inconsistent with the previous results that expression of CHS and CHI genes was positively correlated with flavonoid accumulation in citrus and apricot [43,44]. Although 'Nongda 5' had low expression of flavonoid biosynthetic genes and relatively lower total flavonoid contents compared to 'Jinou 1' and 'Nongda 3', its antioxidant abilities were higher than many fruit species [45], suggesting there might be some other bioactive compounds that contribute to its high antioxidant abilities.…”
Section: Discussioncontrasting
confidence: 99%
“…Supportively, Oude Griep et al have demonstrated that the ability of fruits and vegetables to treat coronary heart diseases varies depending on their color [46]. Furthermore, these findings corroborate with reports in other fruit crops [12,14,47]. All DAMs in pairwise comparisons between groups were identified, providing fundamental data for in-depth exploration of the variation in bioactive compounds among the four different colored BMPs.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, the phenylalanine metabolic pathway offers an alternate route for the biosynthesis of specific isoflavonoids and flavonol compounds [20,21]. The biosynthesis of flavonoid compounds is tightly regulated by various biosynthetic enzymes and genes, including PAL, 4CL, CHS, FLS, and F3 ′ H [22,23]. In our study, we employed ELISA and qPCR techniques to evaluate the influence of humic acid on these pivotal biosynthetic enzymes involved in flavonoid compound production.…”
Section: Discussionmentioning
confidence: 99%